Active and passive mechanisms drive secretory granule biogenesis during differentiation of the intestinal parasite Giardia lamblia - Gottig, Natalia (2006)
The parasitic protozoan Giardia lamblia undergoes important changes to survive outside the intestine of its host by differentiating into infective cysts. During encystation, three cyst wall proteins (CWPs) are specifically expressed and concentrated within encystation-specific secretory vesicles (ESVs). ESVs are electron-dense secretory granules that transport CWPs before exocytosis and extracellular polymerization into a rigid cyst wall. Because secretory granules form at the trans-Golgi in higher eukaryotes and because Giardia lacks an identifiable Golgi apparatus, the aim of this work was to investigate the molecular basis of secretory granule formation in Giardia by examining the role of CWPs in this process. Although CWP1, CWP2, and CWP3 are structurally similar in their 26-kDa leucine-rich overlapping region, CWP2 is distinguished by the presence of a 13-kDa C-terminal basic extension. In non-encysting trophozoites, expression of different CWP chimeras showed that the CWP2 basic extension is necessary for biogenesis of ESVs, which occurs in a compartment derived from the endoplasmic reticulum. Nevertheless, the CWP2 basic extension per se is insufficient to trigger ESV formation, indicating that other domains in CWPs are also required. We found that CWP2 is a key regulator of ESV formation by acting as an aggregation factor for CWP1 and CWP3 through interactions mediated by its conserved region. CWP2 also acts as a ligand for sorting via its C-terminal basic extension. These findings show that granule biogenesis requires complex interactions among granule components and membrane receptors.